2004
DOI: 10.2166/wst.2004.0059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a rapid polymerase chain reaction based identification technique for Vibrio cholerae isolates

Abstract: Rapid and accurate identification of waterborne pathogens, such as Vibrio cholerae, in drinking-water sources is important to enable effective resource management and public health protection. Phenotypic systems currently being used for the identification of Vibrio cholerae isolates are time-consuming and the need exists for the development of suitable molecular techniques that can offer both fast and reliable identification. During this study, isolates identified as Vibrio cholerae by means of two different b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The specificity of these primers was confirmed using DNA probes (Nandi et al, 2000). Le Roux et al (2004) have evaluated and identified a combination of three primers for the detection of V. cholerae ompW gene in environmental isolates. Their work has shown that the PCR approach is more specific than the API 20E and VITEK 32 systems in identifying environmental V. cholerae strains.…”
Section: Pcr Detection Of Unique Gene Fragmentsmentioning
confidence: 97%
“…The specificity of these primers was confirmed using DNA probes (Nandi et al, 2000). Le Roux et al (2004) have evaluated and identified a combination of three primers for the detection of V. cholerae ompW gene in environmental isolates. Their work has shown that the PCR approach is more specific than the API 20E and VITEK 32 systems in identifying environmental V. cholerae strains.…”
Section: Pcr Detection Of Unique Gene Fragmentsmentioning
confidence: 97%
“…These systems have been used to identify biothreat agents such as Bacillus anthracis (20), Yersinia spp. (16,183), Vibrio cholerae (176), and other pathogens (219). BiOLOG has recently introduced a "dangerous pathogen" supplement (DP Database) to its MicroLog system, although no published evaluations of the system are available currently.…”
Section: Automated Biochemical Testsmentioning
confidence: 99%
“…It is associated but not limited to estuarine systems. V. cholerae is known to persist in inland freshwater systems (le Roux et al, 2004). Efforts to manage and mitigate cholera outbreaks invariably start with bacteriological monitoring of aquatic ecosystems, a procedure that is considered essential for the tracking of V. cholerae O1 (Binsztein et al, 2004).…”
Section: Introductionmentioning
confidence: 99%